ANALYSIS OF THE REALIZATION OF MOTOR VEHICLE TAX RECEIPTS AT THE BAUBAU CITY SAMSAT OFFICE - Laode Muhammad Hasrul Adan; Jeki Julian Amin (JIAR : Journal Of International Accounting Research, 2024)
Motor Vehicle Tax (PKB) is one of the main sources of Regional Original Income (PAD) which has great potential in supporting regional development. However, the realization of PKB revenue in Baubau City is not optimal due to the low level of taxpayer compliance, the limited effectiveness of the policy, and obstacles in the administrative system. This study aims to analyze the realization of PKB revenue at the Baubau City Samsat Office, identify the factors that influence it, and evaluate the effectiveness of the tax amnesty policy. This study uses a quantitative descriptive approach with trend analysis techniques and comparisons to PKB revenue data for the 2017 period. Data were obtained from the Baubau Samsat report and interviews with Samsat officers and taxpayers. The results of the study indicate that although the tax amnesty policy can increase tax revenue in the short term, in the long term this policy risks reducing tax compliance. Other factors that influence PKB revenue include the quality of Samsat services, the level of tax socialization, and the economic conditions of the community. The implications of this study emphasize the need to optimize service digitalization, increase tax education, and evaluate tax amnesty policies to improve taxpayer compliance in a sustainable manner.